The Effects of Vitamin D-K-Calcium Co-Supplementation on Endocrine, Inflammation, and Oxidative Stress Biomarkers in Vitamin D-Deficient Women with Polycystic Ovary Syndrome: A Randomized, Double-Blind, Placebo-Controlled Trial - Razavi, M.; Jamilian, M.; Karamali, M.; Bahmani, F.; Aghadavod, E.; Asemi, Z. (Hormone and Metabolic Research, 2016)
The current study was conducted to assess the effects of vitamin D-K-calcium co-supplementation on endocrine, inflammation, and oxidative stress biomarkers in vitamin D-deficient women with polycystic ovary syndrome (PCOS). This randomized double-blind, placebo-controlled trial was performed on 60 vitamin D-deficient women diagnosed with PCOS aged 18–40 years old. Participants were randomly allocated into 2 groups to intake either 200 IU vitamin D, 90 μg vitamin K plus, 500 mg calcium supplements (n=30), or placebo (n=30) twice a day for 8 weeks. Endocrine, inflammation, and oxidative stress biomarkers were quantified at the beginning and the end of the study. After 8 weeks of intervention, compared with the placebo, vitamin D-K-calcium co-supplementation resulted in a significant reduction in serum-free testosterone (− 2.1±1.6 vs.+0.1±1.0 pg/ml, p<0.001) and dehydroepiandrosterone sulfate (DHEAS) levels (− 0.8±1.0 vs.−0.1±0.5 μg/ml, p=0.006). In addition, a significant increase in plasma total antioxidant capacity (TAC) (+ 75.7±126.1 vs.−80.4±242.8 mmol/l, p=0.005) and a significant difference in plasma malondialdehyde (MDA) concentrations (+ 0.03±0.6 vs.+1.4±2.4 μmol/l, p=0.005) was observed following the supplementation with vitamin D-K-calcium compared with the placebo. A trend toward a greater decrease in luteinizing hormone was observed in vitamin D-K-calcium co-supplement group compared to placebo group (− 7.0 vs.−1.2 IU/l, p=0.09). We did not find any significant effect of vitamin D-K-calcium co-supplementation on prolactin, follicle-stimulating hormone, 17-OH progesterone, inflammatory markers, and glutathione levels. Overall, vitamin D-K-calcium co-supplementation for 8 weeks among vitamin D-deficient women with PCOS had beneficial effects on serum DHEAS, free testosterone, plasma TAC, and MDA levels.
Keywords: vitamin supplementation; polycystic ovary syndrome; endocrine; inflammation; oxidative stress